2022
DOI: 10.1111/mec.16504
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes respond predictably to built habitats on the seafloor

Abstract: The seafloor contains complex ecosystems where habitat heterogeneity influences biodiversity. Natural biological and geological features including vents, seeps and reefs create habitats that select for distinct populations of micro‐ and macrofauna. While largely studied for macrobiological diversity, built habitats may also select distinct microbiomes. Built habitat density on the seafloor is increasing with ocean sprawl expanding in the continental shelf and slope, potentially having widespread effects on ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…This study paves the way for applying high throughput data to measure attributes of biodiversity, and its resilience to anthropogenic modification. The paper by Hampel et al (2022) showed that the presence of undersea "built habitats" (shipwrecks) causes increased microbial biodiversity and a predictable core microbiome in their surrounding deep-sea sediments (extending up to 300 m from the wrecks). Specific archaeal groups showed enrichment around shipwrecks, suggesting metabolic shifts towards chemolithoautotrophy in these proximate sediments.…”
Section: Inva S Ive S Pecie S/ Homog Eniz Ationmentioning
confidence: 99%
See 2 more Smart Citations
“…This study paves the way for applying high throughput data to measure attributes of biodiversity, and its resilience to anthropogenic modification. The paper by Hampel et al (2022) showed that the presence of undersea "built habitats" (shipwrecks) causes increased microbial biodiversity and a predictable core microbiome in their surrounding deep-sea sediments (extending up to 300 m from the wrecks). Specific archaeal groups showed enrichment around shipwrecks, suggesting metabolic shifts towards chemolithoautotrophy in these proximate sediments.…”
Section: Inva S Ive S Pecie S/ Homog Eniz Ationmentioning
confidence: 99%
“…(2022). Another supervised learning method was used to make predictions of sediment sample proximity to shipwrecks based on frequency of microbial taxa (Hampel et al., 2022). Machine learning inference methods paired with eco‐evolutionary simulation models can additionally identify the ecological and evolutionary processes that interact to generate biodiversity patterns, as demonstrated by Overcast et al.…”
Section: Invasive Species/homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabarcoding approaches can clearly identify the effect of anthropogenic habitat modification on species assemblages, including key taxa that are associated with modified environments, as well as the overall homogenizing effects of invasions. For example, Hampel et al (Hampel, Moseley, & Hamdan, 2022) show that the presence of undersea "built habitats" (shipwrecks) causes increased microbial biodiversity and a predictable core microbiome in their surrounding deep-sea sediments (extending up to 300m from the wrecks). Specific archaeal groups showed enrichment around shipwrecks, suggesting metabolic shifts towards chemolithoautotrophy in these proximate sediments.…”
Section: Cross Scale Interactions and Microbiomesmentioning
confidence: 99%
“…Incorporation of Deep Learning / Artificial Intelligence approaches applied to image analysis to study arthropod biodiversity . Supervised learning was used to make predictions of sediment sample proximity to shipwrecks based on frequency of microbial taxa (Hampel et al, 2022).…”
Section: Recurring Themesmentioning
confidence: 99%